Providing Personal Data in the Procedure of Preventive Examinations - Sobczyk, Arkadiusz (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The subject of the analysis is to determine the legal position of participants in proceedings to determine an employee’s ability to work. In particular, the subject of the argument is that the employer may, and even has an obligation to, provide the occupational physician with information about the employee’s health.